Single low-dose primaquine for blocking transmission of Plasmodium falciparum malaria – a proposed model-derived age-based regimen for sub-Saharan Africa - (:unkn) unknown (My University, 2018)
BACKGROUND: In 2012, the World Health Organization recommended blocking the transmission of Plasmodium falciparum with single low-dose primaquine (SLDPQ, target dose 0.25 mg base/kg body weight), without testing for glucose-6-phosphate dehydrogenase deficiency (G6PDd), when treating patients with uncomplicated falciparum malaria. We sought to develop an age-based SLDPQ regimen that would be suitable for sub-Saharan Africa.METHODS:Using data on the anti-infectivity efficacy and tolerability of primaquine (PQ), the epidemiology of anaemia, and the risks of PQ-induced acute haemolytic anaemia (AHA) and clinically significant anaemia (CSA), we prospectively defined therapeutic-dose ranges of 0.15-0.4 mg PQ base/kg for children aged 1-5 years and 0.15-0.5 mg PQ base/kg for individuals aged ≥6 years (therapeutic indices 2.7 and 3.3, respectively). We chose 1.25 mg PQ base for infants aged 6-11 months because they have the highest rate of baseline anaemia and the highest risks of AHA and CSA. We modelled an anthropometric database of 661,979 African individuals aged ≥6 months (549,127 healthy individuals, 28,466 malaria patients and 84,386 individuals with other infections/illnesses) by the Box-Cox transformation power exponential and tested PQ doses of 1-15 mg base, selecting dosing groups based on calculated mg/kg PQ doses.RESULTS:From the Box-Cox transformation power exponential model, five age categories were selected: (i) 6-11 months (n = 39,886, 6.03%), (ii) 1-5 years (n = 261,036, 45.46%), (iii) 6-9 years (n = 20,770, 3.14%), (iv) 10-14 years (n = 12,155, 1.84%) and (v) ≥15 years (n = 328,132, 49.57%) to receive 1.25, 2.5, 5, 7.5 and 15 mg PQ base for corresponding median (1st and 99th centiles) mg/kg PQ base of: (i) 0.16 (0.12-0.25), (ii) 0.21 (0.13-0.37), (iii) 0.25 (0.16-0.38), (iv) 0.26 (0.15-0.38) and (v) 0.27 (0.17-0.40). The proportions of individuals predicted to receive optimal therapeutic PQ doses were: 73.2 (29,180/
Keywords: African Research